Wire flame sprayed aluminium coatings onto polymer and CFRP substrates - Lunn, Geoffrey David (2018)
Fibre reinforced polymer matrix composites (FRPs) are used in an increasing number of applications because of their attractive mechanical properties such as high specific strength and stiffness. However, for a number of applications, enhanced surface properties such as thermal and electrical conductivity and resistance to wear are required. Thermal spray coatings have the potential to be a technically suitable and cost effective means of achieving these surface properties. This thesis is a systematic study of the deposition of wire flame sprayed (WFS) pure aluminium onto two different carbon fibre reinforced polymer (CFRP) substrates; one epoxy and one PEEK based as well as unreinforced epoxy, PEEK and steel substrates.